El impacto de la reforma tributaria ecuatoriana en el régimen RIMPE - Allayca Tenesaca, Edgar Ramiro (2025)
In Latin America, tax reforms focused on small-scale businesses seek to counteract economic inequality. That is why the Organic Law of Ecuador on Tax Simplification and Progressivity introduced the Simplified Regime for Entrepreneurs and Popular Businesses (RIMPE) which seeks to simplify tax compliance, administrative and fiscal burden for small taxpayers by improving and influencing investment decisions, The European Commission has recently launched a study on the role of microenterprises in the world economy. Thus, this study aimed to evaluate the impact of RIMPE on the tax burden and fiscal management in Ecuador, The European Commission has been working with the Member States to ensure that the EU’s structural policy is consistent with the Community’s objectives. The methodology used was a mixed methodology that combined qualitative and quantitative approaches, including analysis of data from the Tax Administration and review of legal and academic documents to fully understand the impact of RIMPE. The analysis showed that the Ecuadorian tax reform has had a significant positive impact. An increase in the number of businesses established and jobs generated was observed due to tax reductions and simplification of the registration process. In addition, transparency and efficiency in fiscal management were improved, increasing the confidence of investors and entrepreneurs. The implementation of RIMPE has facilitated the creation and expansion of businesses in Ecuador, contributing to economic growth and social development. While challenges such as tax culture remain, the reform has laid a solid foundation for balancing tax collection with stimulating sustainable business growth.